2015
DOI: 10.1038/srep16372
|View full text |Cite
|
Sign up to set email alerts
|

Broadband and enhanced nonlinear optical response of MoS2/graphene nanocomposites for ultrafast photonics applications

Abstract: Due to their relatively high compatibility with specific photonic structures, strong light-matter interactions and unique nonlinear optical response, two-dimensional (2D) materials, such as graphene and transition metal dichalcogenides, are attractive for ultrafast photonics applications. Here, we fabricate MoS2/graphene nanocomposites by a typical hydrothermal method. In addition, we systematically investigate their nonlinear optical responses. Our experiments indicate that the combined advantages of ultrafas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 185 publications
(76 citation statements)
references
References 58 publications
(75 reference statements)
3
73
0
Order By: Relevance
“…[30] This shift could also be attributed to the transition of the bulk material toward monolayer, for which a smaller Raman shift between the E 2g and A 1g modes is expected. [10] Crucially, prominent D + G peaks characteristic of CC vibrations were observed at ≈1300-1580 cm −1 , [5,26] which indicate the presence of carbon domains in the 2D f-MoS 2 nanoparticle, consistent with the TEM and XPS analysis. The peaks were also found to broaden after laser treatment due to covalent functionalization, consistent with that reported previously for MoSe 2 .…”
supporting
confidence: 71%
See 1 more Smart Citation
“…[30] This shift could also be attributed to the transition of the bulk material toward monolayer, for which a smaller Raman shift between the E 2g and A 1g modes is expected. [10] Crucially, prominent D + G peaks characteristic of CC vibrations were observed at ≈1300-1580 cm −1 , [5,26] which indicate the presence of carbon domains in the 2D f-MoS 2 nanoparticle, consistent with the TEM and XPS analysis. The peaks were also found to broaden after laser treatment due to covalent functionalization, consistent with that reported previously for MoSe 2 .…”
supporting
confidence: 71%
“…
biomedicine, [2,3] tribology, [4] photonics, [5] and electrocatalysis, [6] among others. Significant progress has been made recently in fabricating and functionalizing 2D nanosheets of transition metal dichalcogenides.
…”
mentioning
confidence: 99%
“…Typically, Zhang et al reported a MoS 2 ‐based Er:Fiber laser with 637 fs duration at 1568 nm, which was the shortest pulse of TMDs‐based saturable absorber . The saturable absorber performance could be enhanced by hybridizing to another 2D materials such as graphene and black phosphorus …”
Section: Nlo Processes In Tmdsmentioning
confidence: 99%
“…[1][2][3] Afterwards, thanks to graphene and other two dimensional (2D) materials, which exhibit large values of the optical conductivity on a broad frequency band, remarkable non-linear optical response and tunability properties were demonstrated. [4][5][6][7][8] In addition, the conjunction of the two concepts above is expected to further boost the research field, thanks to the huge potential offered by 2D materials patterned as a metasurface [9][10][11] and by hybrid devices where a metallic metasurface is coupled to 2D conductors. [12][13][14] Whether based on 2D materials, traditional metals, or innovative alloys, 15 a (structured) optically conducting surface (OCS) shows a certain degree of energy loss, due to the very nature of the conductors which constitute the device.…”
mentioning
confidence: 99%